Kingdom of the Netherlands-Curacao and Sint Maarten : 2022 Article IV Consultation Discussions-Press Release; and Staff Report. (IMF Staff Country Reports; Country Report, 2022)
The economies of Curacao and Sint Maarten are recovering from the pandemic but facing multiple challenges, including spillovers from the war in Ukraine. Curacao was in a protracted recession even before the pandemic due to spillovers from the Venezuelan crisis. Sint Maarten needs to fully recover not only from the pandemic, but also from the devastating 2017 hurricanes.